Dapog Multi Tray Innovation to Improve the Efficiency of Rice Seed Seedbeds (International Journal of Scientific Research in Science and Technology, 2024)
To achieve food self-sufficiency, the application of agricultural technology of seeding tools and machines is important. To support rice cultivation, rice planting machines have been found and widely applied, rice planting machines or what is called rice transplanters. The increasing need for the availability of seeds requires innovation to modify unit dapog into multi-tray, with the purpose of the research to reduce the realization of dapog or seedbed box innovation in plurality so that it can reduce operational steps and produce uniform seed growth. This research offers a new approach to the design of multi-tray innovations that, at the same time cut between the dividers according to the size of the mold. Using a combination method includes 1) Qualitative to design the tool based on user input and needs analysis and 2) Quantitative to measure the performance and effectiveness of the tool after the prototype is completed. Descriptive analysis of the results of the function test and performance of the prototype. The result of the innovation in the form of a multi-try dapog with a size of 18 x 56 cm is preceded by observation of the accuracy of the selection of materials and their thickness, and it is hoped that when the mold is lifted, each square can be automatically separated so that it is easier to lift or roll it. Design in the form of an iron dapog with a width of 18 cm deep, a length of 58 cm, and a set of 10 dapog, made three designs with different thicknesses. 2 x 10 mm, 15 x 30 mm, 30 x 30 mm, each set of 10 units. The innovation of multi-tray dapog to improve the efficiency of rice seed seedbeds has an impact on the development of theory and practice of seeding tools and machine technology, including enriching the understanding or theory of the seedbed process by using a structured tray system, which allows improving the quality of rice seeds in a more controlled manner and increases productivity and practice in the form of the success of rice seed seedbeds, saving time and human resources, as well as making it easier for farmers to manage seed nurseries.